Impact of severe acute respiratory syndrome coronavirus 2 on ectopic pregnancy management in the United Kingdom: a multicentre observational study. (14th June 2021) - Platts, S; Ranawaka, J; Oliver, R; Patra‐Das, S; Kotabagi, P; Neophytou, C; Shah, N; Toal, M; Bassett, P; Davison, A; Gbegbaje, M; Rao, K; et al.
Abstract : Objective: To describe the impact of coronavirus disease 2019 (COVID‐19) on the management of women with ectopic pregnancy. Design: A multicentre observational study comparing outcomes from a prospective cohort during the pandemic [COVID‐19‐ectopic pregnancy registry (CEPR)] compared with a historical pre‐pandemic cohort [non‐COVID‐19‐ectopic pregnancy registry (NCEPR)]. Setting: Five London university hospitals. Population and methods: Consecutive patients diagnosed clinically and/or radiologically with ectopic pregnancy (March 2020–August 2020) were entered into the CEPR and results were compared with the NCEPR cohort (January 2019–June 2019). An adjusted analysis was performed for potentially confounding variables. Main outcome measures: Patient demographics, management (expectant, medical and surgical), length of treatment, number of hospital visits (non‐surgical management), length of stay (surgical management) and 30‐day complications. Results: Three hundred and forty‐one women met the inclusion criteria: 162 CEPR and 179 NCEPR. A significantly lower percentage of women underwent surgical management versus non‐surgical management in the CEPR versus NCEPR (58.6%; 95/162 versus 72.6%; 130/179; P  = 0.007). Among patients managed with expectant management, the CEPR had a significantly lower mean number of hospital visits compared with NCEPR (3.0, interquartile range [IQR] [3, 5] versus 9.0, [5, 14]; P  = <0.001). Among patients managed with medical management, the CEPR had a significantly lower median number of hospital visits versus NCEPR (6.0, [5, 8] versus 9, [6, 10]; P  = 0.003). There was no observed difference in complication rates between cohorts. Conclusion: Women were found to undergo significantly higher rates of non‐surgical management during the COVID‐19 first wave compared with a pre‐pandemic cohort. Women managed non‐surgically in the CPER cohort were also managed with fewer hospital attendances. This did not lead to an increase in observed complication rates. Tweetable abstract: A higher rate of non‐surgical management of ectopic pregnancy during the COVID‐19 pandemic did not increase complication rates. Tweetable abstract: A higher rate of non‐surgical management of ectopic pregnancy during the COVID‐19 pandemic did not increase complication rates.